The reality of using virtual laboratory in Madrasati platform for Chemistry subject teachers in secondary schools in Riyadh - Al-Baqami, Abdallah Saltan; Al-Zahrani, Turki Saad (Journal of Educational and Psychological Sciences, 2024)
The current study aimed to reveal the reality of using virtual laboratory in the Madrasati platform for chemistry teachers in the secondary level in Riyadh. As well as, knowing the training needs for teachers, and the requirements for using virtual classrooms in the Madrasati platform. Besides, knowing the skills necessary to use virtual classrooms in the Madrasati platform, and overcome obstacles that I use in the Madrasati platform from the point of view of chemistry teachers in the secondary level in Riyadh. To achieve the goals of the research, the researcher used the analytical descriptive approach, and applied the questionnaire tool as a main tool in the research to reveal the reality of using virtual laboratory in the Madrasati platform for teachers of the chemistry subject in the secondary level in Riyadh. The sample of the study consisted of 363 male and female teachers of the chemistry subject in the secondary level in the East of Riyadh Education District. After collecting data, statistical processing of the data was carried out, so that the statistical package for social studies (SPSS) program was used to obtain the results of the study. The results of the study reached: 1-There is an urgent need to use and activate the training needs for implementing virtual classrooms on the Madrasati platform. The results of the study also showed. 2-There are skills that chemistry teachers lack when using virtual classrooms on the Madrasati platform, the most important of which is the skill of creating the best methods and methods that help develop and disseminate knowledge. 3-There are major obstacles to using virtual classrooms on the Madrasati platform, including the lack of a sufficient number of computers. In light of this, the study recommended, Study recommended: Holding training courses for teachers to clarify the importance and effectiveness of virtual laboratories on the Madrasati platform and their advantages in teaching and learning and increasing the number of devices used in schools.